The Influence Of Price, Promotion, and Brand Image on INK Helmet Purchase Decision (Study of INK Helmet User on Diponegoro University Students ) - Faizin, Faizin; Hidayat, Wahyu; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
In the past three years, the motorcycle industry in Indonesia has increased. It affects the growth of the helmet industry to provide a comfortable and safe riding environment so that competition among helmet producers in Indonesia getting tougher. Helmet manufacture in Indonesia competed to create a quality product for the customers. INK helmet is one of helmet brand that has been in Indonesia’s helmet industry for a long time, but in the last two years INK helmet market shares has decreased due to the arrival of great competitor,  KYT helmet. The fluctuation of market share has encouraged this study.This study aimed to analyze the influence of  price, promotion, and brand image on the purchasing decision of INK helmet. Respondents who are involved in this study were 98 students, while methods used both are multi stage sampling, and purposive sampling. Data collected by spreading questionnaire and data analysis method was done through multiple linear regressions using SPSS software.Regression results indicate that the variable of price has positive and significant influence on purchase decisions toward INK helmet. Promotion variables have positive and significant impact on purchasing decisions. Brand image variables have positive and significant impact on purchasing decisions Coefficient of determination value amounted, this means purchase decision is influenced by variable price, promotion, and brand image, while the remaining can be explained by other variables that are not investigated in this study.Advice to this research is INKhelmet company have to always make an innovation, increase the promotion, , and quality of product also always giving an affordable price so INK helmet can survive on this tight competition